PERAN AKTIF INSTITUT TRANSPORTASI DAN LOGISTIK (ITL) TRISAKTI DALAM SOSIALISASI LOGISTIK HALAL [HALAL LOGISTICS SOCIALIZATION IN THE LOGISTICS SOCIETY IN JAKARTA] - Raden Didiet Rachmat Hidayat; Sandriana Marina; Aisyah Rahmawati; Reza Fauzi Jayasakti; Lira Agusinta (Jurnal Sinergitas PKM & CSR, 2021)
Law Number 33 of 2014 concerning Halal Product Guarantee (JPH) and Government Regulation Number 31 of 2019 concerning JPH Implementation Regulations have been issued for the halal industry which continues to grow its market share both in the world and in Indonesia. This industry requires a Logistics Service Provider (LSP) company that is halal certified or commonly called halal logistics for storage and distribution services with transportation services in it. Apart from products and processes, halal logistics readiness has an important role in supply chain management as a factor in the Halal Assurance System (HAS). The purpose of this community service activity is to socialize halal logistics to stakeholders who will be directly involved in halal logistics activities. This outreach activity was carried out by providing partners with a framework of halal logistics, Halal Assurance System (SJH) and Halal Logistics opportunities in Indonesia. The method of delivering Halal Logistics socialization materials is carried out by using offline and on-line meetings, discussions and questions and answers. The result of this activity is the increased knowledge and understanding of the community regarding halal logistics. BAHASA INDONESIA ABSTRACT: Undang-Undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal (JPH) serta Peraturan Pemerintah Nomor 31 Tahun 2019 tentang Peraturan Pelaksanaan JPH telah dikeluarkan untuk industri halal yang terus berkembang pangsa pasarnya baik di dunia maupun di Indonesia. Industri ini membutuhkan perusahaan Logistics Service Provider (LSP) yang bersertifikat halal atau biasa disebut logistik halal untuk jasa penyimpanan dan distribusi dengan jasa transportasi didalamnya.  Selain di bidang produk dan proses, kesiapan logistik halal mempunyai peranan penting dalam manajemen rantai pasokan sebagai salah satu faktor Sistem Jaminan Halal (SJH). Tujuan kegiatan pengabdian kepada masyarakat ini adalah mensosialisasikan halal logistik kepada para stakeholder yang akan terlibat langsung dalam aktifitas halal logistik. Kegiatan sosialisasi ini dilaksanakan dengan memberikan kerangka pikir dari logistik halal, Sistem Jaminan Halal (SJH) serta peluang Logistik Halal di Indonesia kepada mitra. Metode penyampaian materi sosialisasi Logistik Halal dilakukan dengan menggunakan pertemuan offline maupun on line, diskusi dan tanya jawab. Hasil kegiatan ini adalah meningkatnya pengetahuan dan pemahaman masyarakat terkait logistik halal.